Vapour–liquid equilibrium study of binary mixtures of aniline with isopropanol, n -butanol and ethylene glycol at the local atmospheric pressure - Mali, P.K.; Mali, N.A.; Yadav, S.S.; Joshi, S.S. (Indian Chemical Engineer, 2018)
The present work analyses the vapour–liquid equilibrium (VLE) behaviour of the binary systems of aniline with isopropanol, n-butanol and ethylene glycol. The isobaric VLE data have been generated at the local atmospheric pressure of 96.15 kPa for all the binary systems of aniline. A dynamic type vapour–liquid circulating VLE still was used for generating the data. Calibration curves were generated using mole fraction and refractive index data for all pairs for composition measurement. The VLE data, generated in T-x,y form for all pairs, were found thermodynamically consistent through the Herington area test and the mean absolute deviation test. Activity coefficient models, Wilson, NRTL and UNIQUAC, were fitted to the data to estimate binary interaction parameters using an objective function of minimising the deviation between the experimental and the calculated total pressure and vapour composition. The experimental data were compared with the model predictions with the estimated parameters and the model predictions were found appropriate. The binary system of aniline and ethylene glycol was found to exhibit azeotropic behaviour at 0.61 mole fraction aniline and 445.1 K.